Human rights, information society and risk society - Rovaletti, María Lucrecia (Acta Bioethica, 2010)
Online bursting obliges to rethink the right to privacy, given the organization of huge databases of personal character. Furthermore, it must be added that the possibility of intercrossing information content may facilitate the control and manipulation of sensible information. These new information and communication technologies (ICT), in continuous development, have expanded also to different health fields, affecting all stakeholders, both users and professionals, public powers and social security organisms. Given the specific stigmatization towards HIV/AIDS, requesting several restrictions for access in those banks is needed and also international norms to deal with the "information society", so that "risk society" does not get worse.